Effects of zearalenone on ovarian development of prepubertal gilts through growth hormone axis - Wu, Fengyang; Gao, Lijie; Li, Fei; Cui, Jia; Yang, Xinyu; Liu, Yanhua; Chen, Saijuan; Chen, Baojiang (Frontiers in Veterinary Science, 2022)
This experiment aimed to establish the effects of zearalenone (ZEN) on ovarian development in prepubertal gilts through the growth hormone axis [growth hormone-releasing hormone (GHRH) / growth hormone (GH) / growth hormone receptor (GHR)]. In a 40-day experiment, forty-eight Landrace × Yorkshire crossbred prepubertal gilts were randomly allocated to four dietary treatments, including a basal diet supplemented with 0 (control), 400 (T1), 800 (T2), and 1600 (T3) μg/kg ZEN. The ovary index of T2 (P = 0.058) and T3 (P = 0.065) increased compared to the control group. Besides, histopathological examination revealed that ZEN promoted the development of ovaries and follicles. The GHR content, relative expression levels of GHR, janus activated kinase 2 (JAK2) mRNA, and mean optical density of GHR in the ovaries of prepubertal gilts in the T2 experimental group increased significantly at P < 0.05 compared to the control group. The T3 group had significantly higher GHR content, relative JAK2 expression levels, and signal transducer and activator of transcriptions 3 (STAT3) mRNA. In conclusion, ZEN enhances the biological effect of GH, promotes the development of the ovary (follicle), and exerts reproductive toxicity by increasing the expression level of GHR, JAK2, and STAT3 mRNA ovary and immune intensity of GHR protein.